The Economics of Density: Evidence from the Berlin Wall - Daniel Sturm; Gabriel Ahlfeldt; Stephen Redding; Nikolaus Wolf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper develops a quantitative model of city structure to separate agglomeration forces, dispersion forces and fundamentals as determinants of location choices. The model remains tractable and amenable to empirical analysis because of stochastic shocks to worker productivity, which yield a gravity equation for commuting ows. To empirically disentangle alternative determinants of location choices, we use Berlin s division and reuni cation as a source of exogenous variation in the surrounding concentration of economic activity. Using disaggregated data on land prices, workplace employment and residence employment for thousands of city blocks for 1936, 1986 and 2006, we nd that the model can account both qualitatively and quantitatively for the observed changes in city structure.
Keywords: N34; O18; R12; 330